AGE-RELATED CHANGES IN PROSTAGLANDIN E2, NITRIC OXIDE, AND VASCULAR ENDOTHELIAL GROWTH FACTOR LEVELS IN GASTRIC MUCOSA DURING THE HEALING OF ACETIC ACID-INDUCED ULCER - Ajayi, Ayodeji Folorunsho; Kehinde, Busuyi David; Lateef, Olubodun Micheal; Akorede, Bolaji Aderibigbe (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Nitric oxide (NO), prostaglandin E2 (PgE2), and vascular endothelial growth factor (VEGF) are fundamental regulators of epithelial restitution and angiogenesis. They play important roles in ulcer healing. Insights into their possible changes during gastric ulcer healing putting age into consideration could give a guide to the proper management of ulcers in the aging population. This study, therefore, examined alterations in the concentrations of PgE2, NO, and VEGF in the gastric mucosa of rats of different ages after induction of ulcer and during healing. Methods: Male Wister rats (aged 3, 6, and 18 months old) were divided into three groups according to their ages. The ulcer was induced using the acetic acid ulcer model. Healing indices studied on days 3, 7, and 14 were the macroscopic dimension of ulcer, stomach tissue concentration of PgE2, NO, and VEGF, with the immunohistochemical expression of VEGF. Results: Outcome of this study showed 100%, 88.36%, and 62.30% area of mucosa healed in 3-, 6-, and 18-month-old rats respectively, on day 14 post-induction of ulcer. PgE2, NO, and VEGF concentrations were inversely proportional to age during healing. Immunohistochemical staining showed that younger rat (3 and 6 months old) had higher expression of VEGF throughout the healing period. Conclusion: It was therefore concluded that the slower rate of healing in older rats could be due to reduced gastroprotection, epithelial restitution, and angiogenesis as age increases.